2021
DOI: 10.3389/feart.2021.681059
|View full text |Cite
|
Sign up to set email alerts
|

What Can Thermal Imagery Tell Us About Glacier Melt Below Rock Debris?

Abstract: Rock debris on the surface of a glacier can dramatically reduce the local melt rate, where the primary factor governing melt reduction is debris layer thickness. Relating surface temperature to debris thickness is a recurring approach in the literature, yet demonstrations of reproducibility have been limited. Here, I present the results of a field experiment conducted on the Canwell Glacier, Alaska, United States to constrain how thermal data can be used in glaciology. These datasets include, 1) a measured sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…More recently, thermal imaging studies have expended temporal coverage. Herreid [14] used three-hour increments over multiple days to determine glacier melt under rock debris. High temporal resolution, such as this study, typically focus on short-term phenomena, such as cooling lava flows [33] .…”
Section: *Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, thermal imaging studies have expended temporal coverage. Herreid [14] used three-hour increments over multiple days to determine glacier melt under rock debris. High temporal resolution, such as this study, typically focus on short-term phenomena, such as cooling lava flows [33] .…”
Section: *Methods Detailsmentioning
confidence: 99%
“…The use of thermal cameras to analyze landscapes has expanded over the last decade (e.g., [ 6 , 14 , 15 , 21 , [32] , [33] , [34] , 39 , 40 ]). However, depending on the type and age of the thermal cameras, the output image may be self-calibrated in radiance, corrected for atmospheric absorption and emission, and each pixel converted to surface temperature values.…”
Section: Introductionmentioning
confidence: 99%
“…At this resolution, local slope and aspect variations, which play an important role in controlling the surface energy balance and therefore the surface temperature, are not captured. Due to the large pixel area of these thermal images, debris, ice cliffs and supraglacial ponds can all appear in a single pixel, resulting in an underestimation of the debris thickness (Rounce and others, 2018; Herreid, 2021). Nicholson and others (2018) showed that ignoring the small-scale variability in debris thickness and using spatially averaged values can have a strong impact on the melt predicted by glacier models, underestimating the ablation rate by 11–30%.…”
Section: Introductionmentioning
confidence: 99%
“…One option to capture surface temperature at a high spatial resolution in glacierized terrain is to use near-surface remote sensing, such as from a plane or uncrewed aerial vehicles (UAVs, Kraaijenbrink and others, 2018) or ground-based oblique imagery (Hopkinson and others, 2010; Aubry-Wake and others, 2015; Herreid, 2021; Tarca and Guglielmin, 2022). These instruments offer the possibility to measure surface temperatures from thermal infrared radiometry (TIR) both at a high spatial resolution and with flexible timing to account for different times of the day or variable weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon might be related to the progressive melting of permafrost at these altitudes and to increasing periglaciar dynamics (Figure 4). It is acknowledged that the upper covers of washout located at some centimeters isolate the ice and reduce the melting process [40][41][42][43][44]. In spite of it, these glaciers are becoming thinner, their velocity is modified, and it has been observed a compression of the ice through the weight of the melt [45].…”
Section: Introductionmentioning
confidence: 99%